Titin‐based mechanosensing modulates muscle hypertrophy. Issue 5 (5th July 2018) - van der Pijl, Robbert; Strom, Joshua; Conijn, Stefan; Lindqvist, Johan; Labeit, Siegfried; Granzier, Henk; Ottenheijm, Coen
Abstract: Background: Titin is an elastic sarcomeric filament that has been proposed to play a key role in mechanosensing and trophicity of muscle. However, evidence for this proposal is scarce due to the lack of appropriate experimental models to directly test the role of titin in mechanosensing. Methods: We used unilateral diaphragm denervation (UDD) in mice, an in vivo model in which the denervated hemidiaphragm is passively stretched by the contralateral, innervated hemidiaphragm and hypertrophy rapidly occurs. Results: In wildtype mice, the denervated hemidiaphragm mass increased 48 ± 3% after 6 days of UDD, due to the addition of both sarcomeres in series and in parallel. To test whether titin stiffness modulates the hypertrophy response, RBM20 ΔRRM and Ttn ΔIAjxn mouse models were used, with decreased and increased titin stiffness, respectively. RBM20 ΔRRM mice (reduced stiffness) showed a 20 ± 6% attenuated hypertrophy response, whereas the Ttn ΔIAjxn mice (increased stiffness) showed an 18 ± 8% exaggerated response after UDD. Thus, muscle hypertrophy scales with titin stiffness. Protein expression analysis revealed that titin‐binding proteins implicated previously in muscle trophicity were induced during UDD, MARP1 & 2, FHL1, and MuRF1. Conclusions: Titin functions as a mechanosensor that regulates muscle trophicity.